Analisis Pengaruh Mutu Pelayanan Keperawatan terhadap Tingkat Kepuasan Pasien di Instalasi Rawat Inap Rumah Sakit Umum Daerah Prof.Dr. Margono Soekarjo Purwokerto - Haryati, Welas; Soenaryo,; Fitriyani, Aris (Jurusan Keperawatan FIKES UNSOED, 2007)
This title is entiled Ã¢â‚¬Å“An Analysis on the Influennce of Nursing Service on PatientsÃ¢â‚¬â„¢ Satisfaction at the Instalation of Bed Care of Prof.Dr. Margono Soekarjo Purwokerto HospitalÃ¢â‚¬Â. The purposive of the research were, firstly, discover whether there is a significanct difference between expected service quality and actual service quality, secondly, to determine bether tangibles, reliability, responsiveness, assurance and emphaty significantly influenced patientsÃ¢â‚¬â„¢ satisfaction, and finaly to determine the most influential variables on patientsÃ¢â‚¬â„¢ satiafaction. There were three Hypothesis proposed in the reseach. The fisrt on stated that there was significant difference between expected service quality and actual service quality. The second one stated that the variables of tangibles, reliability, responsiveness, assurance and emphaty significantly influenced patientsÃ¢â‚¬â„¢ satisfaction do exist. Reseach methodology adopted was survey and the data collection methods were using questionnaires and documentation. The tools of analisis used were t-test ( comparative ), multiple regretions, F-test and t-test. The following result were obststained from the analisis first, which means that Ho must be rejected while Ha is assepted. The acceptance of Ha implies that there is a significant difference between the expected service and actual service quality. Second, F test result showed a significant valuae less than alpha value 0,05. This means that Ho must be rejected while Ha is accepted. The acceptance of Ha implies that all independent variables simultaneously influence patientsÃ¢â‚¬â„¢ satisfaction; third t-test result showed that responsiveness has no significant influence on patientsÃ¢â‚¬â„¢ satiafaction. There fore the revised regretion equation is a follow: Y = - 1,274 + 0,229 X1 + 0,146 X2 + 0,226 X4 + 0,210 X5, means while the result to elasticity test showed that assurance was the most influential variables with an elasticity value of 0,345 greater than other. Based on the findings, it is suggested to the hospital management that empathy, assurance, tangibles and reliability must be continuously improved in order to satisfy the hospital patientsÃ¢â‚¬â„¢.